Efficacy and safety analysis of chemotherapy combined with immunotherapy compared with standard chemotherapy for advanced biliary tract malignant tumors - Zhengfeng Zhang; Dazhen Wang; Liu Yang; Lu Zhao; Lei Yang; Jianji Zhang; Changjie Lou (Cancer Medicine, 2023)
Abstract Objective The treatment of biliary tract (BTC) cancer remains relatively limited, especially in the setting of advanced BTC. Immune checkpoint inhibitors (ICIs) have shown some effects in a variety of solid tumors, but their efficacy and safety in patients with advanced BTC are still elusive, which require in‐depth analysis. Methods The clinical information of 129 patients diagnosed with advanced BTC between 2018 and 2021 were retrospectively reviewed. All patients were treated with chemotherapy, while a portion of them (64 patients) were treated with ICIs, the other 64 patients were not. Therefore, we divided the patients into two groups, SC (standard chemotherapy) and CI (chemotherapy in combined with immunotherapy), then we analyzed the benefit of adding ICIs according to efficacy, adverse events, progression‐free survival (PFS), progressive disease (PD), and the influence of various factors and effectiveness. Results The mean PFS was 9.67 months for CI group and 6.83 months for SC group. The PFS was prolonged by 2.84 months with ICI addition, and the difference was statistically significant (t = 3.114, 95% CI: 1.06–4.74, p < 0.001). The objective response rate (ORR) was 32.81% (21/64) for the CI group versus 10.77% (7/65) for the SC group, and the disease control rate (DCR) was 79.69% (51/64) versus 67.69% (44/65), respectively. Regression analysis showed that factors such as changes in CA19‐9, the level of PD‐L1 expression, tobacco and alcohol, and the neutrophil–lymphocyte (NLR) ratio all influenced PFS (p < 0.05 for all these factors). For the treatment‐related adverse events (TRAEs), the highest grade 3–4 adverse effects were thrombocytopenia in 7.75% (10/129) and neutropenia in 3.1% (4/129), immune‐related adverse events (irAEs) occurred in 32.8% (21/64), and all were grade 1–2. Conclusions Our results showed that ICIs combined with chemotherapy exhibited good antitumor activity with acceptable safety and could be recommended as first‐line treatment for patients with advanced BTC.